Experimental investigation of strong-field-ionization theories for laser fields from visible to midinfrared frequencies - Lai, Yu Hang; Xu, Junliang; Szafruga, Urszula B.; Talbert, Bradford K.; Gong, Xiaowei; Zhang, Kaikai; Fuest, Harald; Kling, Matthias Friedrich; Blaga, Cosmin I.; Agostini, Pierre; Dimauro, Louis F. (Physical Review A, 2017)
Strong-field-ionization yield versus intensity is investigated for various atomic targets (Ne, Ar, Kr, Xe, Na, K, Zn, and Mg) and light polarization from visible to mid-infrared (0.4-4 μm), from multiphoton to tunneling regimes. The experimental findings (normalized yield vs intensity, ratio of circular to linear polarization and saturation intensities) are compared to the theoretical models of Perelomov-Popov-Terent'ev (PPT) and Ammosov-Delone-Krainov (ADK). While PPT is generally satisfactory, ADK validity is found, as expected, to be much more limited.
CRIS-Team Scopus Importer:2023-04-20